PENGARUH CELEBRITY ENDORSER, ELECTRONIC WORD OF MOUTH DAN MEDIA SOSIAL TERHADAP KEPUTUSAN PEMBELIAN PRODUK MS GLOW DI LAZADA - Hutapea, Rusliana; Nofrizal, Nofrizal (Jurnal Daya Saing, 2023)
This study aims to determine: (1) the influence of celebrity endorsers on purchasing decisions of ms.glow on lazada, (2) the effect of electronic word of mouth on purchasing decisions of ms.glow on lazada, (3) the influence of social media on purchasing decisions of ms.glow on lazada, and the influence of celebrity endorsers, electronic word of mouth, and social media on purchasing decisions for ms glow at Lazada. This study used a descriptive method by collecting primary data by distributing questionnaires to a sample of 100 respondents who were at least 17 years old. The results obtained from this study are (1) there is a significant influence of celebrity endorser, on the purchasing decision of ms. word of mouth, the purchase decision for ms glow on lazada is said to have a sig value of 0.006 <0.05 and a t-count value of 2.814 > 1.98498, (3) there is a significant influence on social media, there is a purchase decision for ms.glow on lazada it is said that the sig value is 0.048 < 0.05 and t value 2.003 > 1.98498, (4) there is a significant influence of celebrity endorsers, electronic word of mouth, and social media on purchasing decisions ms. glow in Lazada said a sig value of 0.000 <0.05 withf count of 16.637 > 2.70